2016
DOI: 10.1038/am.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of charge coherence in soft molecular organic semiconductors via the suppression of thermal fluctuations

Abstract: Organic semiconductors are already widely used in electronics. Nevertheless, their fundamental properties are still being debated. In particular, charge transport, which determines the performance of organic light-emitting diodes, solar cells and organic field-effect transistors, has been described by a wide range of complementary but incompatible theories. These theories involve either localized charge carriers hopping from molecule to molecule, leading to incoherent charge transport, or delocalized charge ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The first attempt in this work is to identify the origin of noise in the state-of-the-art organic single-crystalline semiconductor C 8 -DNBDT-NW, where the charge carrier undergoes coherent band-like transport. The band-like carrier transport in the present single crystal form of C 8 -DNBDT-NW was unambiguously verified by the Hall effect measurements and electron spin resonance spectroscopy 33,34 . Previous studies about the 1/f noise in disordered organic semiconductors have revealed that the 1/f noise in I D originates mainly from carrier number fluctuation (δn), i.e., δI ∝ e(δn)μ [23][24][25][26] , which is referred to as McWhorter's model (see "Methods" section) 35,36 .…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The first attempt in this work is to identify the origin of noise in the state-of-the-art organic single-crystalline semiconductor C 8 -DNBDT-NW, where the charge carrier undergoes coherent band-like transport. The band-like carrier transport in the present single crystal form of C 8 -DNBDT-NW was unambiguously verified by the Hall effect measurements and electron spin resonance spectroscopy 33,34 . Previous studies about the 1/f noise in disordered organic semiconductors have revealed that the 1/f noise in I D originates mainly from carrier number fluctuation (δn), i.e., δI ∝ e(δn)μ [23][24][25][26] , which is referred to as McWhorter's model (see "Methods" section) 35,36 .…”
Section: Resultsmentioning
confidence: 74%
“…Note that the exponent q in the power law of temperature dependence, μ ∝ T q , is estimated to be q = −0.83 ± 0.04, which is almost identical to that previously observed for C 8 -DNBDT-NW 34 . This gives confidence that at least in this temperature regime, band-like transport is realized 33,34 . At temperatures down from 215 K, the noise amplitude increases remarkably, while the mobility rapidly diminishes (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…STM tip and sample) can often be divided into two, non exclusive, limits [20,21] where the electron can (i) tunnel directly between the contacts but mediated by the molecule or (ii) tunnel onto the molecule and off again, but with an energy relaxation (due to inelastic phonon scattering) as it resides on the molecule. The first limit describes coherent tunnelling (maintaining phase information) while the second is incoherent.…”
Section: Outline Theoretical Descriptionmentioning
confidence: 99%
“…It is known that spin relaxation in organic semiconductors depends on their carrier transport mechanisms. Carrier transport in pentacene is believed to be intermediate between band-like and hopping conduction (Sakai et al, 2016;Nakayama et al, 2017), varying depending on the morphology of the material. Therefore, determination of the relation between carrier transport and morphology is a central issue for spintronic applications of pentacene.…”
mentioning
confidence: 99%